2019
DOI: 10.1007/s00204-019-02627-y
|View full text |Cite
|
Sign up to set email alerts
|

Absence of neurotoxicity and lack of neurobehavioral consequences due to exposure to tetrabromobisphenol A (TBBPA) exposure in humans, animals and zebrafish

Abstract: Tetrabromobisphenol A (2,2′,6,6′-tetrabromo-4,4′-isopropylidenediphenol, CAS no. 79-94-7) (TBBPA) is an effective brominated flame retardant present in many consumer products whose effectiveness is attributable to its ability to retard flames and consequently save human lives. Toxicokinetic studies revealed that TBBPA when absorbed via the gastrointestinal tract is rapidly metabolized to glucuronide or sulfate metabolites which are rapidly eliminated by the kidney. TBBPA does not accumulate in the body and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 44 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…TBBPA was the only FRC that produced widespread mRNA expression changes where the nervous system was not the primary target. This was consistent with the observation that TBBPA did not alter zebrafish behavior and that the nervous system was not a direct target of this FRC as reviewed in Kacew and Hayes (2020). Instead, TBBPA primarily impacted pathways that affect synthesis and targeting of proteins that enter the endoplasmic reticulum, as well as translation, which may explain the significant morphological defects observed.…”
Section: Lipid Metabolism and Other Frc-disrupted Biological Processessupporting
confidence: 88%
“…TBBPA was the only FRC that produced widespread mRNA expression changes where the nervous system was not the primary target. This was consistent with the observation that TBBPA did not alter zebrafish behavior and that the nervous system was not a direct target of this FRC as reviewed in Kacew and Hayes (2020). Instead, TBBPA primarily impacted pathways that affect synthesis and targeting of proteins that enter the endoplasmic reticulum, as well as translation, which may explain the significant morphological defects observed.…”
Section: Lipid Metabolism and Other Frc-disrupted Biological Processessupporting
confidence: 88%
“…The neurobehavioral effects of HBCD had also been reported, whereas the neurobehavioral effects of TBBPA were unequivocal. Kacew and Hayes (2020) suggest that TBBPA did not appear to target the brain and was not considered as a neurotoxicant . Our results showed that mice in the three BFR (BDE-209, TBBPA, and HBCD)-exposed group had shorter dwell times in the target quadrant and irregular trajectories.…”
Section: Discussionmentioning
confidence: 45%
“…Extensive in vitro studies have indicated that TBBPA has various toxicities, including neurotoxicity, immunotoxicity, reproductive toxicity, and nuclear receptor-mediated disrupting activities. A major concern regarding TBBPA is that it has the potential to affect thyroid hormone (TH) actions due to its structural resemblance to TH. , Many studies demonstrated thyroid disruption caused by TBBPA may have implications for TH-dependent development alterations in vertebrates such as Xenopus laevis , zebrafish, and so on. However, not all in vitro results agree with in vivo findings from animal studies. For example, neurotoxicity of TBBPA was observed in several cell lines, , but most of mammal studies found no adverse effects associated with exposure to TBBPA. , Recently, Yin et al reported that TBBPA upregulated expression of Notch signaling target genes ( hes1 and hes5 ) in embryonic stem cells differentiating to neurons, suggesting Notch activation and contributing to neural differentiation . Given crucial roles of Notch signaling in vertebrate development and tissues homeostasis, this new finding warrants further studies, particularly in vivo .…”
Section: Introductionmentioning
confidence: 97%
“…For example, neurotoxicity of TBBPA was observed in several cell lines, 19,20 but most of mammal studies found no adverse effects associated with exposure to TBBPA. 21,22 Recently, Yin et al reported that TBBPA upregulated expression of Notch signaling target genes (hes1 and hes5) in embryonic stem cells differentiating to neurons, suggesting Notch activation and contributing to neural differentiation. 23 Given crucial roles of Notch signaling in vertebrate development and tissues homeostasis, this new finding warrants further studies, particularly in vivo.…”
Section: ■ Introductionmentioning
confidence: 99%